Semi-Auto Dosing Robot with Image Processing (ELEKTRIKA- Journal of Electrical Engineering, 2021)
This paper describes the Semi-Auto Dosing Robot with Image Processing (SADR-IP) that is applied in the agriculture field. The SADR-IP is developed mainly to automate and replace the human watering plants process. The concept and the design of this project are convenient, easy to activate, and monitor throughout the crop field. The image processing based on PyCharm is employed for this robot allows us to increase the speed and accuracy of the work. In addition, various types of crops can be identified by using this image processing technology so that the robot can dose the correct amount of water as needed. Two Arduino Uno boards are used to move the robot and dosing process with a servo motor. The results show that the SADR-IP is reliable to be implemented in the agriculture field. In addition, the use of PyCharm for Image Processing makes the robot design very new in the dosing robot category due to its practicality for detecting different types of crops.